Attachment Security in Infancy: A Preliminary Study of Prospective Links to Brain Morphometry in Late Childhood - Leblanc, Élizabel; Dégeilh, Fanny; Daneault, Véronique; Beauchamp, Miriam H.; Bernier, Annie (Frontiers in Psychology, 2017)
A large body of longitudinal research provides compelling evidence for the critical role of early attachment relationships in children’s social, emotional, and cognitive development. It is expected that parent-child attachment relationships may also impact children’s brain development, however, studies linking normative caregiving experiences and brain structure are scarce. To our knowledge, no study has yet examined the associations between the quality of parent-infant attachment relationships and brain morphology during childhood. The aim of this preliminary study was to investigate the prospective links between mother-infant attachment security and whole-brain gray matter volume and thickness in late childhood. Attachment security toward the mother was assessed in thirty-three children when they were 15 months old. These children were then invited to undergo structural magnetic resonance imaging at 10-11 years of age. Results indicated that children more securely attached to their mother in infancy had larger gray matter volumes in the superior temporal sulcus and gyrus, temporo-parietal junction, and precentral gyrus in late childhood. No associations between attachment security and cortical thickness were found. If replicated, these results would suggest that a secure attachment relationship and its main features (e.g., adequate dyadic emotion regulation, competent exploration) may influence gray matter volume in brain regions involved in social, cognitive, and emotional functioning through experience-dependent processes.